REAKSI PASAR DAN EFISIENSI PASAR ATAS KEBIJAKAN TARIF IMPOR AMERIKA SERIKAT: EVENT STUDY PADA SAHAM LQ45 - Exsanda Cahya Pradita; Mahatma Kufepaksi (Yayasan Nusantara Hasana Berdikari, 2026)
This study aims to analyze market reactions and test semi-strong market efficiency in response to the announcement of the US import tariff policy on stocks included in the LQ45 Index. This testing was conducted through abnormal return analysis and trading volume activity (TVA) during the event period. The research method used was a quantitative event study approach. The sample consisted of 37 companies that met the purposive sampling criteria from the LQ45 stock group. The observation period spanned eleven trading days: five days before the event (T-5), the day of the event (T0), and five days after the event (T+5). Data analysis was conducted using descriptive statistics, normality tests, and hypothesis testing using the One Sample Test and the Wilcoxon Signed Ranks Test, in accordance with the characteristics of the data distribution. The results indicate that the announcement of the US import tariff policy contained information that was responded to by the Indonesian capital market. This response was reflected in changes in abnormal returns and stock trading volume activity around the announcement date. The research findings indicate that investors reacted to the increasing global economic uncertainty triggered by US international trade policies. This condition suggests that the announced information can influence investment decisions and stock trading dynamics in the LQ45 stock group.